PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS CANVA DENGAN PENDEKATAN TEORI VAN HIELE PADA MATERI MENGONSTRUKSI SERTA MENGURAI KUBUS DAN BALOK UNTUK SISWA FASE C SEKOLAH DASAR - Dila Aerin Septiani; Khaila Azzahra Syaqib; Sa'adah Nuraeni; Alfiana Nurussama; Teten Ginanjar Rahayu (STKIP Subang, 2025)
This research is motivated by the need for interactive learning media to help elementary school students understand geometry of three-dimensional shapes, particularly in constructing and deconstructing cubes and rectangular prisms, which are abstract in nature. This study aims to examine the feasibility of mathematics learning media on three-dimensional geometry materials through validation by media experts and subject-matter experts, as well as to test the practicality of the CUBYLAND media through student response questionnaires. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 22 sixth-grade elementary school students. Data were collected through subject-matter expert validation sheets, media expert validation sheets, and student response questionnaires. The validation results showed that the learning media obtained a feasibility percentage of 95.96% from subject-matter experts and 90.90% from media experts, with an average of 93.43%, which falls into the “very feasible” category. The implementation results indicated that students gave positive responses to the aspects of visual appearance, ease of use, and engagement in learning. Based on the evaluation results, Canva-based learning media using the Van Hiele theory approach are declared feasible and practical to be used as an alternative mathematics learning media in elementary schools.